Nitrous oxide emissions from clover in the Mediterranean environment - Volpi, Iride; Bosco, Simona; Nassi o Di Nasso, Nicoletta; Triana, Federico; Roncucci, Neri; Laville, Patricia; Neri, Simone; Virgili, Giorgio; Bonari, Enrico (Italian Journal of Agronomy, 2016)
Introducing nitrogen N2-fixing crops into cereal-based crop rotations reduces N-fertiliser use and may mitigate soil emissions of nitrous oxide (N2O). However, the effect of the cultivation of N2-fixing crops on N2O emissions is still not well understood. N2O from N2-fixing crops can be emitted in two ways: during biological N2 fixation itself and when legume residues are returned to the soil. A field trial was carried out on clover (Trifolium squarrosum Savi) to test the role of leguminous crops on N2O emissions in the Mediterranean environment. Monitoring was performed from December 2013 to September 2014. Cumulated N-N2O fluxes were calculated for the growing season (Phase 1) and the post-harvest period (Phase 2) in order to assess the importance of each phase. Our results did not show statistically significant differences between the two phases in term of contribution to the total cumulative N-N2O emissions, in fact Phase 1 and Phase 2 accounted respectively for 43 and 57% of the total.